A feasibility randomized controlled trial of a community-level physical activity strategy for older adults with motoric cognitive risk syndrome - Hernon, Shannon M.; Singh, Yashi; Ward, Nathan; Kramer, Arthur F.; Travison, Thomas G.; Verghese, Joe; Fielding, Roger A.; Kowaleski, Christopher; Reid, Kieran F. (Frontiers in Aging, 2024)
The motoric cognitive risk syndrome (MCR) is a syndrome characterized by subjective memory complaints and slow walking speeds that can identify older adults at increased risk for developing Alzheimer’s disease or a related dementia (ADRD). To date, the feasibility of community-based physical activity (PA) programs for improving outcomes in MCR have yet to be examined. To address this knowledge gap, we conducted a translational randomized controlled trial (RCT) comparing 24-weeks of PA to a healthy aging education (HE) control intervention delivered within the infrastructure of an urban senior center in Greater Boston (clincaltrials.gov identifier: NCT03750682). An existing senior center employee was trained to administer the multimodal group-based PA program that included moderate-intensity aerobic walking, strength, flexibility and balance training. A total of 79 older adults attended the senior center for a screening visit, of whom 29 met the MCR criteria and 25 were randomized to PA or HE (mean age: 74.4 ± 7 years; BMI: 32.4 ± 7 kg/m2; 85% female; 3MSE score: 92.4 ± 7; gait speed: 0.52 ± 0.1 m/s; SPPB score 4.8 ± 1.9). Due to the Covid-19 pandemic the study was stopped prematurely. Participants could successfully adhere to the study interventions (overall attendance rate: PA: 69% vs. HE:70% at study termination). Participants also successfully completed baseline and follow-up study assessments that included a computerized cognitive testing battery and objective tests of physical performance and functional exercise capacity. No study-related adverse events occurred. Notable trends for improved cognitive performance, gait speed and 6-min walk distance were exhibited in PA compared to HE. Our study provides important preliminary information to aid the design of larger-scale RCTs of PA that may help to preserve the independence of vulnerable older adults at high risk for ADRD in community-based settings.